2014
DOI: 10.1523/jneurosci.0167-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Arc Regulates Experience-Dependent Persistent Firing Patterns in Frontal Cortex

Abstract: The brain encodes information about past experience in specific populations of neurons that communicate with one another by firing action potentials. Studies of experience-dependent neural plasticity have largely focused on individual synaptic changes in response to neuronal input. Indicative of the neuronal output transmitted to downstream neurons, persistent firing patterns are affected by prior experience in selective neuronal populations. However, little is known about the molecular and cellular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…4D), which showed increased visual homotopic correlation and increased visual-anterior area anticorrelation. One statistically significant PC was also found in the WT-NV vs. WT-MD correlation difference ( mice have normal lateral geniculate nucleus anatomy and visual cortex retinotopy (42), and cortical neuron membrane excitability is not altered (43). Additionally, Arc −/− mice have precritical period visual-evoked potentials that are identical to those found in WT (42).…”
Section: Arc-nv N=8mentioning
confidence: 81%
See 1 more Smart Citation
“…4D), which showed increased visual homotopic correlation and increased visual-anterior area anticorrelation. One statistically significant PC was also found in the WT-NV vs. WT-MD correlation difference ( mice have normal lateral geniculate nucleus anatomy and visual cortex retinotopy (42), and cortical neuron membrane excitability is not altered (43). Additionally, Arc −/− mice have precritical period visual-evoked potentials that are identical to those found in WT (42).…”
Section: Arc-nv N=8mentioning
confidence: 81%
“…Importantly, prior studies have shown that Arc gene deletion does not alter growth curves, visual system anatomy, visual cortex retinotopic maps, visual-evoked potentials, or cortical neuron membrane excitability (42)(43)(44). Thus, the experience-dependent processes that were attenuated in Arc −/− mice are not attributable to disrupted basic visual functionality, but to specific action of Arc on experience-driven synaptic change.…”
Section: Monocular Visual Deprivation Induces Intranetwork Change In mentioning
confidence: 93%
“…We demonstrate that the normal EPSP summation and spike firing in layer 5 pyramidal neurons, driven by bursts of activity in hippocampal afferents, is significantly attenuated after activity-dependent LTD of NMDAR transmission. Previous studies have underlined the importance of NMDAR transmission in temporal summation between pairs of PFC pyramidal neurons, where they may play a key role in recurrent excitation (48) and persistent firing (49). Such effects may contribute to working memory processes in PFC.…”
Section: Discussionmentioning
confidence: 99%
“…Arc expression is induced by motor learning in motor cortical neurons (Hosp et al, 2013; Ren et al, 2014), and application of protein synthesis inhibitors to motor cortex (Dayan and Cohen, 2011; Kleim et al, 2003; Luft et al, 2004) or genetic knockout of Arc (Ren et al, 2014) disrupts long-term motor learning behavior. However, the cellular process by which Arc is involved in motor learning remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This task robustly activates neurons in motor cortical areas and increases the level of Arc expression (Costa et al., 2004; Ren et al, 2014). Therefore, this rotarod training task is well suited for the study of neuronal recruitment and consolidation in motor learning.…”
Section: Introductionmentioning
confidence: 99%